Further Reflections on the Therapy Training Program in Aarhus, and the Role of Case Studies in Psychotherapy Research - Hougaard, Esben (Pragmatic Case Studies in Psychotherapy, 2008)
This paper responds to commentaries by Edwards (2008) and Huppert, Carmeli, and Gilon (2008) on the case study of a special format of intensive, group cognitive-behavioral therapy for social phobia in an Anxiety Clinic run by the Department of Psychology of the University of Aarhus in Denmark (Hougaard et al., 2008). My response addresses the following topics: 1) case studies and evidence-based practice; 2) the evidence-basis of the Aarhus treatment program; 3) mechanisms of change in psychotherapy; 4) the Aarhus clients and their treatment in the program; 5) the Aarhus trainees and their learning; and 6) differences between the training program of Huppert et al. in Jerusalem and our Aarhus program.